Harmonic Mitigation Using a Polarized Ramp-time Current-Controlled Inverter - Hanny H. Tumbelaka; Lawrence J. Borle (Universitas Ahmad Dahlan, 2010)
This paper describes the implementation of a shunt active power filter for a three-phase four-wire system to overcome the power quality problems generated by mixed non-linear loads which are a combination of harmonic, reactive and unbalanced components. The filter consists of a three-phase current-controlled voltage source inverter (CC-VSI) with a filter inductor at the AC output and a DC-bus capacitor. The CC-VSI is operated to directly control the grid current in order to be sinusoidal and in phase with the grid voltage without sensing the load currents. The switching is controlled by using polarized ramp-time current control, which is based on the concept of zero average current error (ZACE) with a fixed switching frequency. The laboratory experiment results indicate that the filter is able to mitigate the harmonics and the reactive power, so that the grid currents are sinusoidal, in phase with the grid voltages, and symmetric although the grid voltage contains harmonics.